(untitled) - Naborov, Vladimir Vladimirovich (New York, NY, 1996)
This is a good collection of some of Nabokov's most diverse work. Ada is a beautiful discourse on philosophy and incest that rivals the classic Lolita. Transparent Things is a short but extremely dense book, written in an amazing narrative; a personal favorite. Look At The Harlequins is a fascinating autobiography told theough the perspective of an author with a parallel life. A very worthy buy
Keywords: American literature,American fiction,Naborov, Vladimir Vladimirovich, 1899 - 1977; 20th century,20th century